1996
DOI: 10.1097/00005650-199605000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Culture of Medical Group Practices

Abstract: Background:The culture of medical group practices is gaining increasing attention as one of the most important organizational factors influencing the costs and quality of health care. Based on organizational theory, we propose that the culture of the practice differs depending on size, ownership, location, and the number of medical specialties.Methods: A survey was sent to 1223 physicians in 191 clinics in the upper Midwest. The clinic response rate was 77%. The survey instrument identifies 9 culture dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…20 We tested the six domains thought to be pertinent to the current study (the first six listed), and found four that remained in the new factor analyses (cohesiveness, trust, quality, and information), while a fifth (leadership values alignment) emerged. Two scales (collegiality and identity) were dropped, as some of their items shifted to the remaining domains.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…20 We tested the six domains thought to be pertinent to the current study (the first six listed), and found four that remained in the new factor analyses (cohesiveness, trust, quality, and information), while a fifth (leadership values alignment) emerged. Two scales (collegiality and identity) were dropped, as some of their items shifted to the remaining domains.…”
Section: Discussionmentioning
confidence: 98%
“…These scales overlap, and further extend Kralewski's work on the structure and culture of medical group practices. 20 These five domains, along with the pace of the office, are associated with multiple physician reactions including satisfaction, stress, tendency to err, and intent to leave the practice. We have thus demonstrated a relationship between organizational climate and undesirable reactions by physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Organizational climate was assessed by incorporating scales selected from Kralewski's multidimensional measure 15 into a factor analysis. We identified 5 domains: (1) A 2-step regression analysis was performed to assess outcomes associated with working part-time.…”
Section: Survey Contentmentioning
confidence: 99%